2017
DOI: 10.1099/mic.0.000396
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the biosynthesis of pyriculol in the rice blast fungus Magnaporthe oryzae

Abstract: Pyriculol was isolated from the rice blast fungus Magnaporthe oryzae and found to induce lesion formation on rice leaves. These findings suggest that it could be involved in virulence. The gene MoPKS19 was identified to encode a polyketide synthase essential for the production of the polyketide pyriculol in the rice blast fungus M. oryzae. The transcript abundance of MoPKS19 correlates with the biosynthesis rate of pyriculol in a time-dependent manner. Furthermore, gene inactivation of MoPKS19 resulted in a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 42 publications
5
46
0
Order By: Relevance
“…Furthermore, two di-terpene cyclase-encoding genes (MGG_01949 and MGG_14722) and three dimethylallyl tryptophane synthase (DMATS)-encoding genes (MGG_06540, MGG_10953, and MGG_12480) were upregulated. MGG_10671, encoding a sesquiterpene synthase, was also upregulated (51)(52)(53). With the exception of OXR1 and CYP1, MoLAEA was not found to alter the expression of genes in the ACE1 cluster (54).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two di-terpene cyclase-encoding genes (MGG_01949 and MGG_14722) and three dimethylallyl tryptophane synthase (DMATS)-encoding genes (MGG_06540, MGG_10953, and MGG_12480) were upregulated. MGG_10671, encoding a sesquiterpene synthase, was also upregulated (51)(52)(53). With the exception of OXR1 and CYP1, MoLAEA was not found to alter the expression of genes in the ACE1 cluster (54).…”
Section: Resultsmentioning
confidence: 99%
“…epipyriculol, epidihydropyriculol, pyriculariol and pyricuol), tenuazonic acid and picolinic acid (PA) were produced by P. oryzae on rice leaves (Kim et al , Tsurushima et al ). The tenuazonic acid, PA and pyriculol are of greater importance for blast symptoms development on rice (Umetsu et al , Yoder , Iwahashi et al , Jacob et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The antimelanogenic effect of compound C-9-H was also analyzed against other melanized fungus viz., Magnaporthe oryzae, Aspergillus terreus, and Aspergillus flavus ( Figure 2). The results revealed that only M. oryzae which produces melanin through DHN polyketide pathway, 25 developed white demelanized colonies at 2.34 mM C-9-H concentration, whereas no demelanization was observed in A. terreus and A. flavus ( Figure 2). A. terreus lacks pksP homolog in melanin biosynthesis pathway, 26 whereas A. flavus produces melanin through non-DHN pathway.…”
Section: Resultsmentioning
confidence: 99%